m6A eraser FTO modulates autophagy by targeting SQSTM1/P62 in the prevention of canagliflozin against renal fibrosis - Yang, Youjing; Li, Qianmin; Ling, Yi; Leng, Linxin; Ma, Yu; Xue, Lian; Lu, Guoyuan; Ding, Yue; Li, Jianzhong; Tao, Shasha (Frontiers in Immunology, 2023)
The dysregulation of autophagy contributes to renal fibrosis. N6-methyladenosine (m6A) RNA modification is a critical mediator of autophagy. Our previous studies have reported that the disorder of PPARα/fatty acid oxidation (FAO) axis in renal tubular cells is suppressed by STAT6, which is involved in the regulation of renal fibrotic processes. Here, we found that canagliflozin significantly upregulates SQSTM1/P62, promoting PPARα-mediated FAO by inducing autophagy-dependent STAT6 degradation both in TGF-β1-treated HK2 cells and in unilateral ureteral occlusion (UUO) and ischemia-reperfusion (I/R) renal fibrosis mouse models. Knockdown of P62/SQSTM1 led to the impairment autophagic flux and the dysregulation of STAT6/PPARα axis, which was confirmed by SQSTM1/P62cKO mice with UUO treatment along with bioinformatics analysis. Furthermore, SQSTM1/P62 deficiency in renal tubular cells inhibited canagliflozin’s effects that prevent FAO disorder in renal tubular cells and renal fibrosis. Mechanistically, the level of m6A eraser FTO, which interacted with SQSTM1 mRNA, decreased in the renal tubular cells both in vitro and in vivo after canagliflozin administration. Decrease in FTO stabilized SQSTM1 mRNA, which induced autophagosome formation. Collectively, this study uncovered a previously unrecognized function of canagliflozin in FTO in the autophagy modulation through the regulation of SQSTM1 mRNA stability in renal tubular STAT6/PPARα/FAO axis and renal fibrosis.